Kaposi sarcoma and vertebral involvement in people with HIV: a case report and systematic literature review - Maria Mazzitelli; Davide Leoni; Alberto Maraolo; Serena Marinello; Lucrezia Calandrino; Angela Panese; Maria Luisa Calabrò; Dario Marino; Vincenzo Scaglione; Annamaria Cattelan (HIV Research & Clinical Practice)
Background Kaposi Sarcoma (KS) has been historically associated with HIV, especially in people with advanced immunosuppression. Its prevalence decreased over time, but management remains difficult especially when the diagnosis is late and there is a visceral involvement. Bone localization, and particularly the vertebral one, is rare. We herein present a case of vertebral localizations of KS and performed a review literature to assess demographic, clinical characteristics and treatment outcomes in people with HIV. Methods The systematic review was carried out by following the PRISMA guidelines and registering the protocol in PROSPERO database (n. registration: CRD42024548626). We included all cases of vertebral localizations of KS from January 1rst 1981 to December 31rst, 2023. Results Twenty-two cases, including ours, were ever reported in people with HIV, mostly males (95.4%), with a median age of 35 years (IQR: 32-44), median CD4+ T cell count of 80 cell/mm3 (IQR 13-111), 31.8% with high HIV viral load. Five people received HIV and KS diagnosis simultaneously. In all cases, but one, there were multiple sites involved. Most spine lesions were localized at thoracic and lumbar levels (59.1%), causing pathological fractures in 2 cases. Chemotherapy and radiotherapy were performed in 50% and 18.2% cases, respectively. 22.7% persons died, stability and improvement/disease regression were reported for 13.6% and 22.7% persons, respectively, while 9.9% had a significant disease progression and a person was lost to follow-up. Conclusions Despite progresses in treatment, late presentation of KS, especially with spine involvement may have a poor prognosis. More efforts are needed to promote access to HIV testing, especially when indicating conditions are present.